An Efficient Solid-Phase Extraction-Based Liquid Chromatography Method to Simultaneously Determine Diastereomers α-Tocopherol, Other Tocols, and Retinol Isomers in Infant Formula - Baifen Huang; Zengxuan Cai; Jingshun Zhang; Jiaojiao Xu (Journal of Food Quality)
The separation and simultaneous quantitation of diastereomers of DL-α-tocopherol, eight tocol forms, and retinols (trans and cis) have been conducted by reversed-phase liquid chromatography followed by solid-phase extraction. A chiral silica stationary phase modified with polysaccharide derivative on the monodisperse macroporous silica gel (Unichiral OD-5H column, 150 mm × 4.6 mm, 5 μm, NanoMicro Technology Co., Ltd.) was employed for eluting each target compound. Instead of conventional solvent extract, a green and eco-friendly solid-phase extraction column, packing with nonpolar polystyrene divinylbenzene, was optimized in terms of capacity and solvent used in steps. Validation of the method was examined and confirmed to be satisfactory, with excellent linearity regression (r > 0.9999), acceptable accuracy (74.66%∼112.92%), and precision (0.20%∼10.52%) results. Limit of detection ranged from 0.05 mg·kg−1 (retinols) to 0.4 mg·kg−1 (tocols). The method was checked by infant formula reference material SRM 1849a as well, which illustrated good agreement of mass fraction with certified value and enriched the important isomer data.